Characterization of the spray drying behaviour of emulsions containing oil droplets with a structured interface. (22nd October 2012) - Serfert, Y.; Schröder, J.; Mescher, A.; Laackmann, J.; Shaikh, M. Q.; Rätzke, K.; Gaukel, V.; Schuchmann, H. P.; Walzel, P.; Moritz, H.-U.; Drusch, S.; Schwarz, K.
Abstract : The aim of this study was to characterize the process of atomization and drying of layer-by-layer emulsions containing lecithin (single layer emulsion) and lecithin/chitosan (bilayer emulsion) and the oxidative stability of the microcapsules during storage. For this purpose, the analysis of the emulsion spray droplet size during two-fluid nozzle and rotary atomization was carried out to identify suitable process parameters. The drying behaviour of single and bilayer emulsions was investigated by calculation of the volume flow density during single-droplet drying during acoustic levitation. In spray-dried solid particles, the oxidative stability in the single layer microcapsules was higher than in the bilayer microcapsules. This was partly attributed to lower microencapsulation efficiency in the bilayer microcapsules compared to the single layer microcapsules. Furthermore, it could be shown, that excess chitosan in the bulk carrier matrix affects the free volume elements and thus oxygen diffusion.